Column Hall of the Noble Club (House of Unions) in Moscow: The Problem of Authenticity and Prototypes - Yakovlev, Alexey N. (Actual Problems of Theory and History of Art, 2022)
The Column Hall of the Noble Club (House of the Unions) in Moscow is one of the masterpieces of architect Matvey Kazakov. The restructuring of the Dolgorukov house for the Nobility Club was carried out in 1785–1787, and the Column Hall was completed in time for the celebration of the 25th anniversary of the accession to the throne of Catherine II. The hall was rebuilt after the fire of 1812. There was no unambiguous opinion in the scientific literature about what the original appearance of the hall was. This article refutes the reconstruction of the Hall without balconies, made by A. M. Kharlamova. Basing on sources, it is proved that the authentic appearance of the hall was recreated during the restoration by A. N. Bakarev exactly as it was before the fire. The main sources are: the Dairy of F. de Miranda and the drawing by L. F. Tishbein, made in 1787. The article also considers a range of possible prototypes of Kazakov’s project. Among them, the most likely source was the Wedding Hall of Louis XVI and Marie Antoinette in Paris, built in 1770.
Keywords: 1812; Matvey Kazakov; Francisco de Miranda; Tischbein; Jean Chalgrin; François Boisot; The Column Hall; Wedding Hall of Louis XVI; classicism; reconstruction; authenticity; prototype